Analytes’ Structure and Signal Response in Evaporating Light Scattering Detector (ELSD) - Dalavitsou, Antonia; Vasiliadis, Alexandros; Mordos, Michail D.; Kouskoura, Maria G.; Markopoulou, Catherine K. (Current Analytical Chemistry, 2019)
Background: Working with an Evaporative Light Scattering Detector (ELSD), the target components are converted to a suspension of particles in a gas phase by a nebulizer and heated while the mobile phase is evaporated. Then, the incident light is directed at the remaining particles which are scattered and detected. Methods: The signal response of an ELS detector is studied through the correlation of the signal intensity of 65 compounds (at 30, 45 and 80°C) with their structural and physicochemical characteristics. Therefore, 67 physicochemical properties as well as structural features of the analytes were inserted as X variables and they were studied in correlation with their signal intensity (Y variable). Results: The collected data were statistically processed with the use of partial least squares method. The results proved that several properties were those that mainly affected the signal intensity either increasing or decreasing this response. Conclusion: The derived results proved that properties related to vapor pressure, size, density, melting and boiling point of the analytes were responsible for changes in the signal intensity. The light detected was also affected by properties relevant to the ability of a molecule to form hydrogen bonds (HBA and HBD) and its polarizability or refractivity, but at a lower extent.
Keywords: HPLC detector